A process for machining an optical lens

By forming an amorphous silicon dioxide layer and applying a temporary protective layer during optical lens processing, combined with ion beam activation and chemical bonding treatment, the problems of insufficient chemical activity on the lens surface, glass powder adhesion, and poor film adhesion are solved, thereby improving the imaging performance and reliability of the lens.

CN123039909APending Publication Date: 2026-11-06SHANGRAO XIZHONG OPTICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611522019.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In existing optical lens processing technology, the surface chemical activity is insufficient after polishing, glass powder adheres during the edge grinding process, the film adhesion is poor after coating, and the ink coating layer is easy to fall off during high-temperature baking, which affects the imaging performance and reliability of the lens.

Method used

After polishing, an amorphous silicon dioxide layer is formed, and a peelable temporary protective layer is applied before edge grinding. The lens surface is activated by ion beam treatment, and the adhesion of the film layer is improved by chemical bonding. When ink is applied, the ink is chemically bonded to the plastic deformation layer to form a chemical anchor.

Benefits of technology

It significantly improves the adhesion and environmental stability of the coating, reduces the whitening and peeling defects of the ink coating, and ensures the imaging performance and reliability of the lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123039909A_ABST
    Figure CN123039909A_ABST
Patent Text Reader

Abstract

This invention relates to the field of optical lens processing technology, and proposes a processing method for optical lenses. The process includes: inspecting a raw glass lens, rough grinding, fine grinding, and polishing; during polishing, controlling the polishing fluid to form an amorphous silica layer on the lens surface; applying a peelable temporary protective layer to the edge area before edge grinding; cleaning and ion beam activation of the ground lens; coating to deposit a first film on the surface of the activated amorphous silica layer; applying ink to chemically bond the ink to the ion beam-activated plastic deformation layer; and finally, inspection and packaging. This invention utilizes the amorphous silica layer as the coating interface, improving film adhesion through silanol-based chemical bonding and flexible stress buffering; using a temporary protective layer to isolate grinding contaminants and maintain the integrity of the amorphous silica layer; and using ion beam activation to simultaneously improve the adhesion of the coating and ink application, reducing ink whitening and peeling defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical lens processing technology, and in particular to a processing technology for optical lenses. Background Technology

[0002] Optical lenses are core optical components in consumer electronics products such as drones, security monitoring systems, and automotive cameras. Their processing quality directly affects imaging performance and product reliability. The processing of optical lenses typically includes processes such as blank inspection, rough grinding, fine grinding, polishing, cleaning, edge grinding, coating, ink application, and finished product inspection.

[0003] In the polishing process, the polishing slurry interacts with the glass surface through a chemical-mechanical process, enabling the lens surface to achieve the specified surface roughness and surface accuracy. The surface condition of the polished lens has a significant impact on the interfacial bonding performance of subsequent coatings and inks. In existing technologies, the lens is usually cleaned after polishing to remove residual polishing slurry and glass debris. However, the surface chemical activity after cleaning may be insufficient, affecting the adhesion of subsequent films or inks.

[0004] During the edge grinding process, a chamfering grinding wheel grinds the edge of the lens. Glass powder and coolant generated during grinding may adhere to the lens surface. Existing technologies typically use methods such as coolant rinsing to reduce powder adhesion. However, under the heat of grinding, some glass powder may still stick to the lens edge, leading to defects such as whitening and uneven adhesion in the subsequent ink coating layer.

[0005] In the coating process, the adhesion between the film and the glass substrate, as well as the film stress, are important factors affecting lens reliability. In existing technologies, the lens surface is typically cleaned or activated before coating to improve film adhesion. However, due to the difference in thermal expansion coefficients between the glass substrate and the film material, residual stress may be generated in the film after coating, potentially leading to cracking or peeling during temperature changes or environmental testing.

[0006] In the inking process, the adhesion of the ink to the lens edge directly affects the durability of the inking layer. In existing technologies, ink adhesion is typically improved by increasing the surface roughness of the lens edge or by cleaning the edge. However, during high-temperature baking and curing, the ink layer may experience decreased adhesion due to shrinkage stress or a mismatch in thermal expansion with the substrate, leading to localized peeling or uneven edges. Summary of the Invention

[0007] In view of the above, the main objective of this invention is to provide a processing technology for optical lenses in order to solve the aforementioned technical problems.

[0008] This invention proposes a processing technology for optical lenses, the process comprising: Step 1: Inspect the raw glass lens to obtain qualified raw lenses; perform coarse grinding and fine grinding on the qualified raw lenses to obtain finely ground lenses. Step 2: Polish the finely ground lens. During the polishing process, the finely ground lens is polished using a polishing pad and polishing fluid. The concentration of the chemically active components of the polishing fluid and the polishing time are controlled to form an amorphous silicon dioxide layer on the surface of the polished lens, resulting in a polished lens with an amorphous silicon dioxide layer. Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer and perform edge grinding. During the edge grinding process, the temporary protective layer is used to isolate the glass powder and coolant generated during grinding. Control the grinding depth and feed speed of the chamfering wheel to form a plastic deformation layer on the chamfered surface of the lens. After edge grinding, remove the temporary protective layer to obtain the edge-ground lens. Step 4: Clean and activate the edged lens with an ion beam. Use an ion beam to remove contaminants from the surface of the edged lens and activate the surface molecules of the amorphous silica layer and the plastic deformation layer to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface. Step 5: Coating the activated lens. During the coating process, a crucible is used to support the film material and deposit the film on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer form chemical bonds with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer is used to buffer the stress caused by the difference in thermal expansion coefficients between the film layer and the glass substrate, thus obtaining the coated lens. Step 6: Apply ink to the coated lens. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer. At the same time, the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining an ink-coated lens. Step 7: Inspect the coated lenses to obtain qualified optical lenses. Package the qualified optical lenses into warehouse to obtain finished lenses.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention significantly improves film adhesion and environmental stability by retaining the amorphous silicon dioxide layer after polishing and using it as the coating interface layer, utilizing the chemical bonding between the silanol group and the film material, and at the same time, using the flexibility of the amorphous silicon dioxide layer to buffer the stress caused by the difference in thermal expansion coefficient between the film layer and the glass substrate.

[0010] 2. This invention effectively isolates the glass powder and coolant generated during grinding from contaminating the edge area of ​​the lens by applying a peelable temporary protective layer before grinding, and removes the protective layer after grinding to keep the amorphous silicon dioxide layer intact, providing a clean and highly chemically active interface for subsequent coating.

[0011] 3. This invention simultaneously treats the amorphous silicon dioxide layer and the plastic deformation layer by ion beam activation, so that the film layer forms a chemical bond with the substrate during coating, and the ink forms a chemical bond and mechanical anchor with the chamfered plastic deformation layer during ink application, which significantly improves the adhesion and uniformity of the ink layer and reduces ink whitening and peeling defects.

[0012] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by means of embodiments of the invention. Attached Figure Description

[0013] Figure 1 This is a flowchart of a processing technology for an optical lens proposed in this invention.

[0014] Figure 2 This is a comparison diagram showing the change in film adhesion with heat treatment time in the processing technology of an optical lens proposed in this invention.

[0015] Figure 3 This is a comparison diagram showing the change in ink adhesion with ion beam activation time in the processing technology of an optical lens proposed in this invention.

[0016] Figure 4 This is a comparison chart showing the rate of ink whitening in the optical lens processing technology proposed in this invention, as a function of the edge grinding coolant temperature. Detailed Implementation

[0017] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0018] These and other aspects of the embodiments of the present invention will become clear from the following description and accompanying drawings. In these descriptions and drawings, some specific embodiments of the present invention are specifically disclosed to illustrate some ways of implementing the principles of the embodiments of the present invention; however, it should be understood that the scope of the embodiments of the present invention is not limited thereto.

[0019] Example 1 Please see Figure 1 This embodiment provides a processing technology for optical lenses, the process including: Step 1: Inspect the raw glass lens. Inspection items include center thickness, radius of curvature, thickness variation, and appearance. Center thickness is measured using a micrometer, and radius of curvature is measured using a height gauge. Qualified raw lenses are then obtained. The qualified raw lenses undergo rough grinding and fine grinding sequentially. Rough grinding uses a D46 diamond grinding wheel at a grinding linear speed of 25 m / s, a feed rate of 500 mm / min, and a depth of cut of 0.03 mm. Fine grinding uses a W28 diamond grinding wheel at a grinding pressure of 0.1 MPa and a grinding speed of 100 rpm. Deionized water is used as the coolant during both rough and fine grinding processes, with a coolant flow rate of 5 L / min and a coolant temperature controlled at 15℃, resulting in a finely ground lens.

[0020] Step 2: Polish the finely ground lens. During the polishing process, the lens is polished using a polyurethane polishing pad and a polishing slurry. The polishing slurry contains cerium oxide abrasive with a particle size of 0.01 μm and a cerium oxide mass concentration of 5%. The pH value of the polishing slurry is 7, the polishing pressure is 0.05 MPa, the polishing speed is 50 rpm, and the polishing time is 5 min. The polishing pad has a hardness of 50 Shore A, a thickness of 0.5 mm, and concentric grooves with a depth of 0.3 mm on its surface. The polishing slurry supply rate is 10 mL / min. The polishing slurry temperature is controlled at 15℃ during the polishing process. This results in an amorphous silicon dioxide layer forming on the surface of the polished lens. The thickness of the amorphous silicon dioxide layer is measured using an ellipsometry and controlled to be within 1 nm, thus obtaining a polished lens with an amorphous silicon dioxide layer.

[0021] Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer. The peelable temporary protective layer uses a thermosetting hydrolytic protective ink with a viscosity of 5000 mPa·s. It is applied to the edge area of ​​the polished lens by screen printing with a mesh count of 100. The dry film thickness after printing is 15 μm, and the curing condition is baking at 120℃ for 20 min. The screen printing stencil is a ring pattern, and the inner diameter of the ring is 0.5 mm smaller than the outer diameter of the optically effective area of ​​the lens, so that the protective layer covers the edge area of ​​the optically effective surface, while the ground edge area of ​​the lens remains exposed. Perform edge grinding, controlling the grinding of the chamfering wheel. The depth of cut and feed rate are adjusted to form a plastic deformation layer on the chamfered surface of the lens. During the edge grinding process, the grinding depth of the chamfering wheel is 0.05 mm, the feed rate is 0.5 mm / min, and deionized water is continuously sprayed as a coolant during the edge grinding process. The coolant temperature is 10℃, and the coolant flow rate is 3 L / min. After edge grinding, the temporary protective layer is removed by rinsing the lens in clean water. Deionized water is used for rinsing at a temperature of 20℃ for 1 min, and the rinsing pressure is 0.1 MPa. After removing the protective layer, ultrasonic cleaning with deionized water is performed with an ultrasonic power of 200 W for 3 min to obtain the edged lens.

[0022] Step 4: Clean and ion beam activate the edged lens. Argon gas with a purity ≥99.999% is used as the working gas, the accelerating voltage is 300V, the accelerating current is 100mA, the processing time is 1min, and the vacuum chamber pressure is 1×10-3Pa. The ion beam uses a radio frequency ion source with a beam diameter of 50mm. During ion beam activation, the lens rotates at 5rpm, and the ion beam incident angle is 30°. After ion beam activation, the activation effect is confirmed by contact angle measurement. The contact angle of the activated lens surface is ≤10°. Coating is performed within 20min after ion beam activation to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface.

[0023] Step 5: Coating the activated lens using electron beam evaporation. A molybdenum crucible is used to support the film material, which has a purity of 99.99% or higher. The vacuum chamber pressure is 1×10⁻² Pa, the electron beam output current is 30 mA, the deposition rate is 0.3 nm / s, the ion-assisted bombardment time is 1 min, and the ion source anode voltage is 200 V. The film material is SiO₂, and the film thickness is 10 nm. Argon gas is used for ion-assisted bombardment at a flow rate of 10 sccm. Before coating, the lens is preheated to 150°C and held at that temperature for 10 min. After coating, compressed air is used for convection cooling at a rate of 5°C / min until the lens is cooled to room temperature. The film is deposited on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer chemically bond with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer buffers the stress caused by the difference in thermal expansion coefficients between the film layer and the glass substrate, resulting in a coated lens.

[0024] Step 6: Apply ink to the coated lens. The ink used has a viscosity of 5000 mPa·s and is applied by spraying. The ink thickness is 5 μm. The ink is an epoxy resin type ink, and the active component of the ink is hydroxyl. The ink is thermosetting in a hot air circulating oven with a nitrogen atmosphere and a wind speed of 1 m / s. The baking temperature after ink application is 120℃, and the baking time is 20 min. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer. At the same time, the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining the ink-coated lens.

[0025] Step 7: Inspect the coated lens. Inspection items include outer diameter, center thickness, surface accuracy, coating area, coating adhesion, and appearance. The coating area is inspected using a tool microscope with an accuracy of 0.02 mm. Coating adhesion is tested using 3M 600 tape, pulled at a 90° angle at a speed of 50 mm / s, repeated three times. No coating peeling is acceptable. Surface accuracy is tested using an interferometer with a wavelength of 632.8 nm; the number of apertures should be ≤0.5, and the number of sub-apertures ≤0.2. Qualified optical lenses are then packaged and stored to obtain the finished lens, designated A1.

[0026] Example 2 This embodiment provides a processing technology for optical lenses, including the following steps: Step 1: Inspect the raw glass lens. Inspection items include center thickness, radius of curvature, thickness variation, and appearance. Center thickness is measured using a micrometer, and radius of curvature is measured using a height gauge. Qualified raw lenses are then obtained. The qualified raw lenses undergo rough grinding and fine grinding sequentially. Rough grinding uses a D50 diamond grinding wheel at a grinding linear speed of 31 m / s, a feed rate of 750 mm / min, and a depth of cut of 0.0425 mm. Fine grinding uses a W24 diamond grinding wheel at a grinding pressure of 0.15 MPa and a grinding speed of 225 rpm. Water-based coolant is used for cooling during both rough and fine grinding processes. The coolant flow rate is 8.75 L / min, and the coolant temperature is controlled at 17.5℃, resulting in a finely ground lens.

[0027] Step 2: Polishing the finely ground lens. During polishing, the lens is polished using a polyurethane polishing pad and polishing slurry. The polishing slurry contains cerium oxide abrasive with a particle size of 0.0325 μm and a cerium oxide mass concentration of 11.25%. The pH value of the polishing slurry is 8, the polishing pressure is 0.075 MPa, the polishing speed is 75 rpm, and the polishing time is 11.25 min. The polishing pad has a hardness of 57.5 Shore A, a thickness of 0.875 mm, and a grid-like groove on its surface with a groove depth of 0.475 mm. The polishing slurry supply rate is 20 mL / min. The polishing slurry temperature is controlled at 18.75℃ during polishing. This results in an amorphous silica layer forming on the polished lens surface. The thickness of the amorphous silica layer is measured using an ellipsometer and controlled to be 25 nm, thus obtaining a polished lens with an amorphous silica layer.

[0028] Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer. The peelable temporary protective layer uses a thermosetting hydrolytic protective ink with a viscosity of 5750 mPa·s. It is applied to the edge area of ​​the polished lens by screen printing with a mesh count of 150. The dry film thickness after printing is 16.25 μm, and the curing conditions are baking at 135℃ for 22.5 min. The screen printing stencil is a ring pattern, and the inner diameter of the ring is 0.875 mm smaller than the outer diameter of the optically effective area of ​​the lens, so that the protective layer covers the edge area of ​​the optically effective surface, while the ground edge area of ​​the lens remains exposed. Perform edge grinding, controlling the grinding depth of the chamfering wheel. The grinding depth and feed rate are adjusted to form a plastic deformation layer on the chamfered surface of the lens. During the edging process, the grinding depth of the chamfering wheel is 0.075 mm, the feed rate is 0.875 mm / min, and deionized water is continuously sprayed as a coolant during the edging process. The coolant temperature is 12.5℃, and the coolant flow rate is 4.75 L / min. After edging, the temporary protective layer is removed by rinsing the lens in clean water. Deionized water is used for rinsing at a temperature of 25℃ for 2 minutes and a pressure of 0.15 MPa. After removing the protective layer, ultrasonic cleaning with deionized water is performed with an ultrasonic power of 250 W for 4.25 minutes to obtain the edged lens.

[0029] Step 4: Clean and ion beam activate the edged lens. Argon gas with a purity ≥99.999% is used as the working gas. The accelerating voltage is 375V, the accelerating current is 150mA, the processing time is 3.25min, and the vacuum chamber pressure is 3×10⁻³Pa. An RF ion source with a beam diameter of 87.5mm is used. During ion beam activation, the lens rotates at 8.75rpm, and the ion beam incident angle is 37.5°. After ion beam activation, the activation effect is confirmed by contact angle measurement; the contact angle of the activated lens surface is ≤10°. Coating is performed within 20min after ion beam activation to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface.

[0030] Step 5: Coating the activated lens using electron beam evaporation. A molybdenum crucible is used to support the film material, which has a purity of 99.99% or higher. The vacuum chamber pressure is 1.25 × 10⁻² Pa, the electron beam output current is 32.5 mA, the deposition rate is 0.425 nm / s, the ion-assisted bombardment time is 2 min, and the ion source anode voltage is 212.5 V. The film material is Al₂O₃, and the film thickness is 32.5 nm. Oxygen is used for ion-assisted bombardment, and the gas flow rate is... The coating thickness is 20 sccm; the lens is preheated to 175℃ and kept at that temperature for 15 min before coating; after coating, compressed air is used for convection cooling at a rate of 6.25℃ / min until it reaches room temperature; the film is deposited on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer form chemical bonds with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer is used to buffer the stress caused by the difference in thermal expansion coefficients between the film and the glass substrate, thus obtaining the coated lens.

[0031] Step 6: Apply ink to the coated lens. The ink used has a viscosity of 5750 mPa·s and is applied by brush, with a thickness of 8.75 μm. The ink is a polyurethane type, and the active component is amino. The ink is thermosetting in a hot air circulating oven with an air atmosphere and a wind speed of 1.5 m / s. The baking temperature after ink application is 135℃, and the baking time is 30 min. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer, while the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining the ink-coated lens.

[0032] Step 7: Inspect the coated lens. Inspection items include outer diameter, center thickness, surface accuracy, coating area, coating adhesion, and appearance. The coating area is inspected using a tool microscope with an accuracy of 0.02 mm. Coating adhesion is tested using 3M 600 tape, pulled at a 90° angle at a speed of 62.5 mm / s, repeated three times. No coating peeling is acceptable. Surface accuracy is tested using an interferometer with a wavelength of 632.8 nm; the number of apertures should be ≤0.5, and the number of sub-apertures ≤0.2. Qualified optical lenses are then packaged and stored to obtain the finished lens, designated A2.

[0033] Example 3 This embodiment provides a processing technology for optical lenses, including the following steps: Step 1: Inspect the raw glass lens blanks. Inspection items include center thickness, radius of curvature, thickness variation, and appearance. Center thickness is measured using a micrometer, and radius of curvature is measured using a height gauge. Qualified raw lenses are then obtained. The qualified raw lenses undergo rough grinding and fine grinding sequentially. Rough grinding uses a D55 diamond grinding wheel at a grinding linear speed of 37.5 m / s, a feed rate of 1000 mm / min, and a depth of cut of 0.055 mm. Fine grinding uses a W20 diamond grinding disc at a grinding pressure of 0.2 MPa and a grinding speed of 350 rpm. Deionized water is used as the coolant during both rough and fine grinding processes, with a coolant flow rate of 12.5 L / min and a coolant temperature controlled at 20℃, resulting in a finely ground lens.

[0034] Step 2: Polishing the finely ground lens. During polishing, the lens is polished using a polyurethane polishing pad and polishing slurry. The polishing slurry contains cerium oxide abrasive with a particle size of 0.055 μm and a cerium oxide mass concentration of 17.5%. The pH value of the polishing slurry is 9, the polishing pressure is 0.1 MPa, the polishing speed is 100 rpm, and the polishing time is 17.5 min. The polishing pad has a hardness of 65 Shore A, a thickness of 1.25 mm, and concentric grooves with a depth of 0.65 mm on its surface. The polishing slurry supply rate is 30 mL / min. The polishing slurry temperature is controlled at 22.5℃ during polishing. This results in an amorphous silica layer forming on the polished lens surface. The thickness of the amorphous silica layer is measured using an ellipsometer and controlled to be 50 nm, thus obtaining a polished lens with an amorphous silica layer.

[0035] Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer. The peelable temporary protective layer uses a thermosetting hydrolytic protective ink with a viscosity of 6500 mPa·s. It is applied to the edge area of ​​the polished lens by screen printing with a mesh count of 200. The dry film thickness after printing is 17.5 μm, and the curing condition is baking at 150℃ for 25 min. The screen printing stencil is a ring pattern, and the inner diameter of the ring is 1.25 mm smaller than the outer diameter of the optically effective area of ​​the lens, so that the protective layer covers the edge area of ​​the optically effective surface, while the ground edge area of ​​the lens remains exposed. Perform edge grinding, controlling the grinding of the chamfering wheel. The depth of cut and feed rate are adjusted to form a plastic deformation layer on the chamfered surface of the lens. During the edging process, the chamfering wheel has a cutting depth of 0.1 mm and a feed rate of 1.25 mm / min. Deionized water is continuously sprayed as a coolant during the edging process, with a coolant temperature of 15℃ and a coolant flow rate of 6.5 L / min. After edging, the temporary protective layer is removed by rinsing the lens in clean water at 30℃ for 3 minutes at a pressure of 0.2 MPa. After removing the protective layer, the lens is ultrasonically cleaned with deionized water at a power of 300 W for 5.5 minutes to obtain the edged lens.

[0036] Step 4: Clean and ion beam activate the edged lens. Argon gas with a purity ≥99.999% is used as the working gas. The accelerating voltage is 450V, the accelerating current is 200mA, the processing time is 5.5min, and the vacuum chamber pressure is 5×10⁻³Pa. An RF ion source with a beam diameter of 125mm is used. During ion beam activation, the lens rotates at 12.5rpm, and the ion beam incident angle is 45°. After ion beam activation, the activation effect is confirmed by contact angle measurement; the contact angle of the activated lens surface is ≤10°. Coating is performed within 20min after ion beam activation to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface.

[0037] Step 5: Coating the activated lens using electron beam evaporation. A molybdenum crucible is used to support the film material, which has a purity of 99.99% or higher. The vacuum chamber pressure is 1.5 × 10⁻² Pa, the electron beam output current is 35 mA, the deposition rate is 0.55 nm / s, the ion-assisted bombardment time is 3 min, and the ion source anode voltage is 225 V. The film material is Al₂O₃, and the film thickness is 55 nm. Argon gas is used for ion-assisted bombardment at a flow rate of 30 kilowatts per minute. sccm; Preheat the lens to 200℃ and keep it warm for 20 minutes before coating; After coating, use compressed air convection cooling at a rate of 7.5℃ / min to cool to room temperature; Deposit the film on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer form chemical bonds with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer is used to buffer the stress caused by the difference in thermal expansion coefficients between the film layer and the glass substrate, thus obtaining the coated lens.

[0038] Step 6: Apply ink to the coated lens. The ink used has a viscosity of 6500 mPa·s and is applied by spraying. The ink thickness is 12.5 μm. The ink is an epoxy resin type ink, and the active component of the ink is isocyanate. The ink is thermosetting in a hot air circulating oven with a nitrogen atmosphere and a wind speed of 2 m / s. The baking temperature after ink application is 150℃, and the baking time is 40 min. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer. At the same time, the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining the ink-coated lens.

[0039] Step 7: Inspect the coated lens. Inspection items include outer diameter, center thickness, surface accuracy, coating area, coating adhesion, and appearance. The coating area is inspected using a tool microscope with an accuracy of 0.02 mm. Coating adhesion is tested using 3M 600 tape, pulled at a 90° angle at a speed of 75 mm / s, repeated three times. No coating peeling is acceptable. Surface accuracy is tested using an interferometer with a wavelength of 632.8 nm; the number of apertures should be ≤0.5, and the number of sub-apertures ≤0.2. Qualified optical lenses are then packaged and stored to obtain the finished lens, designated A3.

[0040] Example 4 This embodiment provides a processing technology for optical lenses, including the following steps: Step 1: Inspect the raw glass lens blanks. Inspection items include center thickness, radius of curvature, thickness variation, and appearance. Center thickness is measured using a micrometer, and radius of curvature is measured using a height gauge. Qualified raw lenses are then obtained. The qualified raw lenses undergo rough grinding and fine grinding sequentially. Rough grinding uses a D60 diamond grinding wheel at a grinding linear speed of 44 m / s, a feed rate of 1250 mm / min, and a depth of cut of 0.0675 mm. Fine grinding uses a W17 diamond grinding wheel at a grinding pressure of 0.25 MPa and a grinding speed of 475 rpm. Water-based coolant is used for cooling during both rough and fine grinding processes. The coolant flow rate is 16.25 L / min, and the coolant temperature is controlled at 22.5℃, resulting in a finely ground lens.

[0041] Step 2: Polishing the finely ground lens. During polishing, the lens is polished using a polyurethane polishing pad and polishing slurry. The polishing slurry contains cerium oxide abrasive with a particle size of 0.0775 μm and a cerium oxide mass concentration of 23.75%. The pH value of the polishing slurry is 10, the polishing pressure is 0.125 MPa, the polishing speed is 125 rpm, and the polishing time is 23.75 min. The polishing pad has a hardness of 72.5 Shore A, a thickness of 1.625 mm, and a grid-like groove on its surface with a groove depth of 0.825 mm. The polishing slurry supply rate is 40 mL / min. The polishing slurry temperature is controlled at 26.25℃ during polishing. This results in an amorphous silica layer forming on the polished lens surface. The thickness of the amorphous silica layer is measured using an ellipsometer and controlled to be 75 nm, thus obtaining a polished lens with an amorphous silica layer.

[0042] Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer. The peelable temporary protective layer uses a thermosetting hydrolytic protective ink with a viscosity of 7250 mPa·s. It is applied to the edge area of ​​the polished lens by screen printing with a mesh count of 250. The dry film thickness after printing is 18.75 μm, and the curing conditions are baking at 165℃ for 27.5 min. The screen printing stencil is a ring pattern, and the inner diameter of the ring is 1.625 mm smaller than the outer diameter of the optically effective area of ​​the lens, so that the protective layer covers the edge area of ​​the optically effective surface, while the ground edge area of ​​the lens remains exposed. Perform edge grinding, controlling the grinding depth of the chamfering wheel. The grinding depth and feed rate are adjusted to form a plastic deformation layer on the chamfered surface of the lens. During the grinding process, the chamfering wheel has a grinding depth of 0.125 mm and a feed rate of 1.625 mm / min. Deionized water is continuously sprayed as a coolant during the grinding process, with a coolant temperature of 17.5℃ and a coolant flow rate of 8.25 L / min. After grinding, the temporary protective layer is removed by rinsing the lens in clean water at 35℃ for 4 minutes at a pressure of 0.25 MPa. After removing the protective layer, the lens is ultrasonically cleaned with deionized water at a power of 350 W for 6.75 minutes to obtain the ground lens.

[0043] Step 4: Clean and ion beam activate the edged lens. Argon gas with a purity ≥99.999% is used as the working gas. The accelerating voltage is 525V, the accelerating current is 250mA, the processing time is 7.75min, and the vacuum chamber pressure is 7×10⁻³Pa. An RF ion source with a beam diameter of 162.5mm is used. During ion beam activation, the lens rotates at 16.25rpm, and the ion beam incident angle is 52.5°. The activation effect is confirmed by contact angle measurement after ion beam activation; the contact angle of the activated lens surface is ≤10°. Coating is performed within 20min after ion beam activation to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface.

[0044] Step 5: Coating the activated lens using electron beam evaporation. A molybdenum crucible is used to support the film material, which has a purity of 99.99% or higher. The vacuum chamber pressure is 1.75 × 10⁻² Pa, the electron beam output current is 37.5 mA, the deposition rate is 0.675 nm / s, the ion-assisted bombardment time is 4 min, and the ion source anode voltage is 237.5 V. The film material is TiO₂, and the film thickness is 77.5 nm. Oxygen is used for ion-assisted bombardment, and the gas flow rate is... The coating thickness is 40 sccm; the lens is preheated to 225℃ and kept at that temperature for 25 min before coating; after coating, compressed air is used for convection cooling at a rate of 8.75℃ / min until it reaches room temperature; the film is deposited on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer form chemical bonds with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer is used to buffer the stress caused by the difference in thermal expansion coefficients between the film and the glass substrate, thus obtaining the coated lens.

[0045] Step 6: Apply ink to the coated lens. The ink used has a viscosity of 7250 mPa·s and is applied by brush to a thickness of 16.25 μm. The ink is a polyurethane type, and the active component is hydroxyl groups. The ink is thermosetting in a hot air circulating oven with an air atmosphere and a wind speed of 2.5 m / s. The baking temperature after ink application is 165℃, and the baking time is 50 min. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer, while the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink to the chamfered surface and obtaining the ink-coated lens.

[0046] Step 7: Inspect the coated lenses. Inspection items include outer diameter, center thickness, surface accuracy, coating area, coating adhesion, and appearance. The coating area is inspected using a tool microscope with an accuracy of 0.02 mm. Coating adhesion is tested using 3M 600 tape, pulled at a 90° angle at a speed of 87.5 mm / s, repeated three times. No coating peeling is acceptable. Surface accuracy is tested using an interferometer with a wavelength of 632.8 nm; the number of apertures should be ≤0.5, and the number of sub-apertures ≤0.2. Qualified optical lenses are then packaged and stored to obtain finished lenses, designated as A4.

[0047] Example 5 This embodiment provides a processing technology for optical lenses, including the following steps: Step 1: Inspect the raw glass lens. Inspection items include center thickness, radius of curvature, thickness variation, and appearance. Center thickness is measured using a micrometer, and radius of curvature is measured using a height gauge. Qualified raw lenses are then obtained. The qualified raw lenses undergo rough grinding and fine grinding sequentially. Rough grinding uses a D64 diamond grinding wheel at a grinding speed of 50 m / s, a feed rate of 1500 mm / min, and a depth of cut of 0.08 mm. Fine grinding uses a W14 diamond grinding wheel at a grinding pressure of 0.3 MPa and a grinding speed of 600 rpm. Deionized water is used as the coolant during both rough and fine grinding processes, with a flow rate of 20 L / min and a temperature controlled at 25°C, resulting in a finely ground lens.

[0048] Step 2: Polishing the finely ground lens. During polishing, the lens is polished using a polyurethane polishing pad and polishing slurry. The polishing slurry contains cerium oxide abrasive with a particle size of 0.1 μm and a cerium oxide mass concentration of 30%. The pH value of the polishing slurry is 11, the polishing pressure is 0.15 MPa, the polishing speed is 150 rpm, and the polishing time is 30 min. The polishing pad has a hardness of 80 Shore A, a thickness of 2.0 mm, and concentric grooves with a depth of 1.0 mm on its surface. The polishing slurry supply rate is 50 mL / min. The polishing slurry temperature is controlled at 30℃ during polishing. This process forms an amorphous silica layer on the polished lens surface. The thickness of the amorphous silica layer is measured using an ellipsometer and controlled to be 100 nm, resulting in a polished lens with an amorphous silica layer.

[0049] Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer. The peelable temporary protective layer uses a thermosetting hydrolytic protective ink with a viscosity of 8000 mPa·s. It is applied to the edge area of ​​the polished lens by screen printing with a mesh count of 300. The dry film thickness after printing is 20 μm, and the curing condition is baking at 180℃ for 30 min. The screen printing stencil is a ring pattern, and the inner diameter of the ring is 2 mm smaller than the outer diameter of the optically effective area of ​​the lens, so that the protective layer covers the edge area of ​​the optically effective surface, while the ground edge area of ​​the lens remains exposed. Perform edge grinding, controlling the grinding of the chamfering wheel. The depth of cut and feed rate are adjusted to form a plastic deformation layer on the chamfered surface of the lens. During the edge grinding process, the grinding depth of the chamfering wheel is 0.15 mm, the feed rate is 2 mm / min, and deionized water is continuously sprayed as a coolant at a temperature of 20℃ and a flow rate of 10 L / min. After edge grinding, the temporary protective layer is removed by rinsing the lens in clean water at a temperature of 40℃ for 5 minutes at a pressure of 0.3 MPa. After removing the protective layer, the lens is ultrasonically cleaned with deionized water at a power of 400 W for 8 minutes to obtain the edged lens.

[0050] Step 4: Clean and ion beam activate the edged lens. Argon gas with a purity ≥99.999% is used as the working gas, the accelerating voltage is 600V, the accelerating current is 300mA, the processing time is 10min, and the vacuum chamber pressure is 9×10-3Pa. The ion beam uses a radio frequency ion source with a beam diameter of 200mm. During ion beam activation, the lens rotates at 20rpm, and the ion beam incident angle is 60°. After ion beam activation, the activation effect is confirmed by contact angle measurement. The contact angle of the activated lens surface is ≤10°. Coating is performed within 20min after ion beam activation to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface.

[0051] Step 5: Coating the activated lens using electron beam evaporation. A molybdenum crucible is used to support the film material, which has a purity of 99.99% or higher. The vacuum chamber pressure is 2×10⁻² Pa, the electron beam output current is 40 mA, the deposition rate is 0.8 nm / s, the ion-assisted bombardment time is 5 min, and the ion source anode voltage is 250 V. The film material is SiO₂, and the film thickness is 100 nm. Argon gas is used for ion-assisted bombardment at a flow rate of 50 sccm. Before coating, the lens is preheated to 250°C and held at that temperature for 30 min. After coating, compressed air is used for convection cooling at a rate of 10°C / min until the lens is cooled to room temperature. The film is deposited on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer chemically bond with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer buffers the stress caused by the difference in thermal expansion coefficients between the film layer and the glass substrate, resulting in a coated lens.

[0052] Step 6: Apply ink to the coated lens. The ink used has a viscosity of 8000 mPa·s and is applied by spraying. The ink thickness is 20 μm. The ink is an epoxy resin type ink with amino groups as the active component. The ink is thermosetting in a hot air circulating oven with a nitrogen atmosphere and a wind speed of 3 m / s. The baking temperature after ink application is 180℃, and the baking time is 60 min. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer. At the same time, the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining the ink-coated lens.

[0053] Step 7: Inspect the coated lenses. Inspection items include outer diameter, center thickness, surface accuracy, coating area, coating adhesion, and appearance. The coating area is inspected using a tool microscope with an accuracy of 0.02 mm. Coating adhesion is tested using 3M 600 tape, pulled at a 90° angle at a speed of 100 mm / s, repeated three times. No coating peeling is acceptable. Surface accuracy is tested using an interferometer with a wavelength of 632.8 nm; the number of apertures should be ≤0.5, and the number of sub-apertures ≤0.2. Qualified optical lenses are then packaged and stored to obtain finished lenses, designated A5.

[0054] Comparative Example 1 Comparative Example 1 provides an optical lens comprising a substrate and a hydrophobic and / or oleophobic coating covering the surface of the substrate. A temporary protective coating is applied to the convex surface of the lens. This temporary protective coating is an inorganic material selected from magnesium fluoride (MgF2), lanthanum fluoride (LaF3), aluminum fluoride (AlF3), or cerium fluoride (CeF3), and is deposited by evaporation in a vacuum container, with a thickness of 1-50 nm. This temporary protective coating increases the surface energy of the lens to at least 15 mJ / m2.

[0055] A removable film is attached to the outer surface of a temporary protective coating. This removable film is an electrostatic film made of a plastic material containing at least 20% by weight of plasticizer, and adheres to the outermost layer of the temporary protective coating by electrostatic adsorption. The removable film covers at least the central portion of the convex surface of the lens, and has at least one surface portion on its first side, comprising at least one adhesion area and at least one non-adhesion area distributed across the surface portion, such that the removable film exhibits intermittent adhesion and / or contact with the lens surface.

[0056] The optical lens is placed in an edging apparatus including a chuck, which is then attached to the lens using a liquid-curable adhesive positioned between the chuck and the lens surface. The edging apparatus includes a diamond grinding wheel to grind the lens edge. The edging operation involves machining the edge or circumference of the eyeglasses to shape it to the required dimensions. During the edging process, a removable protective film protects a temporary protective coating from mechanical degradation caused by friction and / or contact during the edging operation.

[0057] After edge grinding, remove any removable film, leaving the temporary protective coating in a state that allows for satisfactory edge grinding of the optical lens. Remove the temporary protective coating to ensure that the optical and surface properties of the hydrophobic and / or oleophobic coating on the lens are identical to those before the protective layer was applied.

[0058] After the lens is ground, it is cleaned and coated to form a functional coating on the lens surface, resulting in a coated lens.

[0059] The coated lens is coated with ink, and black ink is applied to the edge of the lens. After baking and curing, the ink-coated lens is obtained.

[0060] The coated lenses are inspected, including outer diameter, center thickness, surface accuracy, coating range, coating firmness, and appearance. Qualified optical lenses are obtained, packaged, and stored to obtain finished lenses, denoted as D1.

[0061] Comparative Example 2 A substrate coated with an anti-wear coating and a scratch-resistant coating is introduced into a vacuum deposition chamber.

[0062] The vacuum deposition chamber is evacuated until a high vacuum is achieved.

[0063] The front surface of the substrate is activated using an argon ion beam. The ion beam activation conditions are: anolyte current 1A, anolyte voltage 100V, and neutralization current 130mA. The ion beam bombards the substrate surface to clean and activate it.

[0064] Ion irradiation is turned off. Various layers of the antireflective coating, including alternating SiO2 and TiO2 layers, are successively evaporated on the front of the substrate. Deposition is performed with ion assistance. A mirror coating and an antifouling coating are further deposited on the antireflective coating to obtain a coated lens.

[0065] The coated lens is coated with ink, and black ink is applied to the edge of the lens. After baking and curing, the ink-coated lens is obtained.

[0066] The coated lenses are inspected, including outer diameter, center thickness, surface accuracy, coating range, coating firmness, and appearance. Qualified optical lenses are obtained, packaged, and stored to obtain finished lenses, denoted as D2.

[0067] Experimental verification was conducted to confirm the effectiveness of the present invention. Experiment 1: Verification of the formation and retention of amorphous silicon dioxide layer after polishing; Experimental methods: An ellipsometer was used to perform non-destructive measurements on the polished lens surface to determine the thickness of the surface layer. Simultaneously, a contact angle meter was used to measure the water droplet contact angle on the polished lens surface.

[0068] Experimental conditions: Both the experimental and control groups used the polishing conditions described in Example 3: the polishing slurry was a cerium oxide abrasive with a particle size of 0.055 μm, a mass concentration of 17.5%, a pH of 9, a polishing pressure of 0.1 MPa, a polishing speed of 100 rpm, and a polishing time of 17.5 min. After polishing, the surface layer of the experimental group was retained; the control group underwent ultrasonic cleaning with deionized water for 5.5 min after polishing, with an ultrasonic power of 300 W and a water temperature of 30℃. Five lenses were taken from each group, and the average value of the measurements was taken. The experimental results are shown in Table 1. Table 1:

[0069] As shown in Table 1, an amorphous silicon dioxide layer with a thickness of 50.3 nm was detected on the surface of the lens in the experimental group, with a contact angle of 8.2°; this layer was not detected in the control group after cleaning, and the contact angle increased to 42.6°. These results indicate that under the polishing conditions of Example 3, an amorphous silicon dioxide layer was formed on the lens surface, and this layer remained on the lens surface after polishing.

[0070] Experiment 2: Verification of the effect of ion beam activation on contact angle; Experimental Method: The contact angle of a water droplet on the lens surface before and after ion beam activation was measured using a contact angle meter. The measurement employed the seated drop method, in which a deionized water droplet was placed on the lens surface, and the contact angle was calculated using an image analysis system.

[0071] Experimental conditions: The experimental group used the ion beam activation conditions of Example 3: argon as the working gas, argon purity ≥99.999%, accelerating voltage 450V, accelerating current 200mA, processing time 5.5min, vacuum chamber pressure 5×10⁻³Pa; the ion beam used was a radio frequency ion source with a beam diameter of 125mm; the lens rotated at 12.5rpm, and the ion beam incident angle was 45°. The control group had the same conditions as the experimental group except that ion beam activation was not performed. Five lenses were taken from each group, and the average value of the measurement results was taken. The experimental results are shown in Table 2. Table 2:

[0072] Table 2 shows that the contact angle of the experimental group after ion beam activation was 5.3°, while the contact angle of the control group without activation was 88.4°. This result indicates that under the ion beam activation conditions of Example 3, the lens surface achieved high activation, and the contact angle met the activation effect requirement of ≤10°.

[0073] Experiment 3: Verification of the effect of temporary protective layer in isolating edge grinding powder; Experimental Method: An experimental group and a control group were set up, with 100 lenses in each group. The experimental group underwent edge grinding after applying a temporary protective layer; the control group underwent edge grinding directly without applying a temporary protective layer. After edge grinding, the percentage of residual powder area at the lens edge was measured using an optical microscope and image analysis software. Both groups of lenses were then coated with ink, and the whitening rate and adhesion pass rate of the ink coating were statistically analyzed.

[0074] Experimental conditions: The experimental group used the temporary protective layer and edge grinding conditions of Example 3: the temporary protective layer used a thermosetting hydrolytic protective ink with a viscosity of 6500 mPa·s, a screen printing mesh of 200 mesh, a dry film thickness of 17.5 μm, and a curing condition of baking at 150℃ for 25 min; during the edge grinding process, the grinding depth of the chamfering wheel was 0.1 mm, and the feed speed was 1.25 mm / min; the edge grinding coolant was deionized water with a temperature of 15℃ and a flow rate of 6.5 L / min. The control group had the same edge grinding conditions as the experimental group except that no temporary protective layer was applied. The experimental results are shown in Table 3. Table 3:

[0075] Table 3 shows that in the experimental group, the residual powder area after edge grinding accounted for 0.8%, the whitening rate of ink coating was 0%, and the ink coating adhesion qualification rate was 100%. In the control group, the residual powder area accounted for 8.5%, the whitening rate of ink coating was 9%, and the ink coating adhesion qualification rate was 91%. These results indicate that under the temporary protective layer and edge grinding conditions of Example 3, the temporary protective layer effectively isolated the glass powder generated during grinding, fundamentally improving the whitening defect. The main cause of whitening is the adhesion of glass powder formed during grinding to the outer edge of the optical lens or an excessively rough grinding wheel leading to an uneven outer edge.

[0076] Experiment 4: Verification of improved ink coating adhesion; Experimental method: Adhesion test was conducted according to the 3M 600 tape adhesion and pull test method: 3M 600 tape was flatly pasted onto the ink-coated area and pulled off at a speed of 75 mm / s in a 90° direction. The test was repeated 3 times, and the percentage of ink layer peeling off was calculated.

[0077] Experimental conditions: The experimental group used the same ink coating conditions as in Example 3: ink viscosity was 6500 mPa·s, ink coating was done by spraying, and the ink thickness was 12.5 μm; the ink was epoxy resin type ink, and the active component was isocyanate; the baking temperature after ink coating was 150℃, and the baking time was 40 min; curing was carried out in a hot air circulating oven under a nitrogen atmosphere with a wind speed of 2 m / s. The control group had the same ink coating conditions as the experimental group, except that the ink did not contain the active component and the lenses were not activated by ion beam. Five lenses were taken from each group, and the average value of the measurements was taken. The experimental results are shown in Table 4. Table 4:

[0078] Table 4 shows that the area of ​​ink peeling off the experimental group after being pulled off three times at 90° with 3M 600 tape was 0.0%; while the area of ​​ink peeling off the control group was 18.2%. This result indicates that under the ink coating conditions of Example 3, the active components in the ink chemically bond with the silanol groups on the surface of the plastic deformation layer. Simultaneously, the ink penetrates into the microstructure of the plastic deformation layer and solidifies, forming a dual adhesion mechanism of chemical bonding and mechanical anchoring, significantly improving the adhesion of the ink coating to the chamfered surface.

[0079] To further verify the actual performance advantages of the technical solution of the present invention compared with the prior art, the lens prepared in Example 3 (A3) was compared with the lenses prepared in Comparative Example 1 (D1) and Comparative Example 2 (D2) for performance comparison tests.

[0080] Three performance indicators—film adhesion, ink adhesion, and ink whitening rate—were selected for comparative verification. Film adhesion is a core indicator for evaluating the reliability of coated lenses; the cross-cut adhesive tape peel test can quantitatively evaluate the bonding strength between the film and the substrate. Ink adhesion directly affects the durability of the ink layer; a 90° pull-off test using 3M 600 tape can quantify the adhesion level of the ink layer. Ink whitening is a common defect in edge ink coating of optical lenses, and its occurrence rate reflects the impact of the edge grinding process on the ink coating quality.

[0081] exist Figure 2 In Comparative Example 1, after polishing and cleaning to remove the amorphous silica layer, the film was directly deposited on the glass substrate. Lacking chemical bonding of silanol groups, and with the inorganic fluoride temporary coating removed after edge grinding, the film adhesion relied mainly on physical adsorption. The detachment area increased from 3.2% to 13.6% with prolonged heat treatment. In Comparative Example 2, although ion beam activation was performed, the activation parameters (anodine voltage 100V, anolyine current 1A) were low, and the amorphous silica layer was not activated simultaneously. The detachment area increased from 1.5% to 6.8%. In Example 3, the silanol groups of the amorphous silica layer were chemically bonded to the film material, and the flexibility buffered the stress caused by the difference in thermal expansion coefficients. The detachment area was only 1.8% after 40 minutes of heat treatment.

[0082] After heat treatment at 200℃ for 40 min, the film peeling area in Example 3 was 1.8%, while that in Comparative Example 1 increased to 13.6% and that in Comparative Example 2 increased to 6.8%. The increase in peeling area in Example 3 (1.8%) was significantly lower than that in Comparative Example 1 (13.6%) and Comparative Example 2 (6.8%), indicating that the present invention achieves better film thermal stability by retaining the amorphous silicon dioxide layer in situ.

[0083] exist Figure 3 In Comparative Example 1, no ion beam activation treatment was performed. No active functional groups were generated on the surface of the chamfered plastic deformation layer, and the ink relied solely on physical anchoring, with the detachment area consistently between 21.5% and 24.3%. Comparative Example 2 underwent ion beam activation, but its activation parameters were only for substrate surface cleaning (anodine voltage 100V, anodine current 1A), resulting in limited activation of the chamfered plastic deformation layer. The detachment area decreased from 18.2% to 6.4%, still failing to meet the 4B qualification standard. In Example 3, the ion beam activation parameters (accelerating voltage 450V, accelerating current 200mA, incident angle 45°) simultaneously acted on the chamfered plastic deformation layer, generating active functional groups on the surface. The detachment area decreased to 1.5% after 6 minutes of activation and tended to stabilize.

[0084] After 8 minutes of ion beam activation, the ink peeling area in Example 3 was 1.2%, compared to 21.5% in Comparative Example 1 and 6.4% in Comparative Example 2. Example 3 met the 4B qualification standard (peeling area <5%) after only 6 minutes of activation, while Comparative Examples 1 and 2 did not. These results demonstrate that the present invention, through the combination of a radio frequency ion source, lens rotation, and a 45° incident angle, achieves sufficient activation of the chamfered plastic deformation layer surface, resulting in chemical bonding between isocyanate groups and silanol groups in the ink, significantly improving ink adhesion.

[0085] exist Figure 4 In Comparative Example 1, an inorganic fluoride temporary protective coating and an electrostatic film were used, which has a different protection mechanism than this invention. Furthermore, no peelable protective ink was applied. During the edge grinding process, the glass powder easily melted and adhered to the lens edge under the grinding heat. The grinding heat intensified as the coolant temperature increased, and the whitening rate rose from 4.5% to 14.6%. In Comparative Example 2, no temporary protective layer was applied, and the whitening rate increased from 2.8% to 9.8%. The thermosetting hydrolytic protective ink in Example 3 isolated the glass powder from direct contact with the lens edge during the edge grinding process. The protective layer could be removed by rinsing with water without residue. The whitening rate was 0% at a coolant temperature of 8°C and only 3.4% even at 24°C.

[0086] When the temperature of the grinding coolant increased from 8°C to 24°C, the whitening rate of the ink coating in Example 3 increased from 0.0% to 3.4%, in Comparative Example 1 from 4.5% to 14.6%, and in Comparative Example 2 from 2.8% to 9.8%. The temporary protective layer in Example 3 effectively isolated the glass powder generated during grinding, keeping the whitening defect at a low level within the range of coolant temperature fluctuations. In contrast, Comparative Examples 1 and 2, lacking an effective isolation mechanism, saw their whitening rates increase significantly with increasing coolant temperature. The defect rate of whitening in the prior art can reach 12.7%, while Example 3 of this invention only has a rate of 3.4% at 24°C, demonstrating a significant improvement.

[0087] In summary, this invention, by controlling the polishing fluid parameters during the polishing process to retain an amorphous silica layer on the lens surface and using it as a coating interface layer, utilizes the chemical bonding between silanol groups and the film material. Simultaneously, the flexibility of the amorphous silica layer buffers the stress generated between the film layer and the glass substrate due to the difference in thermal expansion coefficients, significantly improving film adhesion and environmental stability. Applying a peelable temporary protective layer before edge grinding effectively isolates the glass powder and coolant generated during grinding from contaminating the lens edge area, keeping the amorphous silica layer intact and providing a clean and highly chemically active interface for subsequent coating. Ion beam activation simultaneously treats the amorphous silica layer and the plastic deformation layer, enabling chemical bonding between the film layer and the substrate during coating, and chemical bonding and mechanical anchoring between the ink and the chamfered plastic deformation layer during ink application. This significantly improves the adhesion and uniformity of the ink coating, reducing ink whitening and peeling defects.

[0088] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0089] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A processing technology for optical lenses, characterized in that, The process includes: Step 1: Inspect the raw glass lens to obtain qualified raw lenses; perform coarse grinding and fine grinding on the qualified raw lenses to obtain finely ground lenses. Step 2: Polish the finely ground lens. During the polishing process, the finely ground lens is polished using a polishing pad and polishing fluid. The concentration of the chemically active components of the polishing fluid and the polishing time are controlled to form an amorphous silicon dioxide layer on the surface of the polished lens, resulting in a polished lens with an amorphous silicon dioxide layer. Step 3: Apply a peelable temporary protective layer to the edge area of ​​the polished lens with an amorphous silica layer and perform edge grinding. During the edge grinding process, the temporary protective layer is used to isolate the glass powder and coolant generated during grinding. Control the grinding depth and feed speed of the chamfering wheel to form a plastic deformation layer on the chamfered surface of the lens. After edge grinding, remove the temporary protective layer to obtain the edge-ground lens. Step 4: Clean and activate the edged lens with an ion beam. Use an ion beam to remove contaminants from the surface of the edged lens and activate the surface molecules of the amorphous silica layer and the plastic deformation layer to obtain an activated lens with an activated amorphous silica layer and an activated plastic deformation layer on the surface. Step 5: Coating the activated lens. During the coating process, a crucible is used to support the film material and deposit the film on the surface of the activated amorphous silica layer. The silanol groups in the activated amorphous silica layer form chemical bonds with the film material, improving the adhesion of the film. At the same time, the flexibility of the amorphous silica layer is used to buffer the stress caused by the difference in thermal expansion coefficients between the film layer and the glass substrate, thus obtaining the coated lens. Step 6: Apply ink to the coated lens. During the ink application process, the active components in the ink chemically bond with the active functional groups on the surface of the activated plastic deformation layer. At the same time, the ink penetrates into the activated plastic deformation layer and cures, thereby improving the adhesion of the ink on the chamfered surface and obtaining an ink-coated lens. Step 7: Inspect the coated lenses to obtain qualified optical lenses. Package the qualified optical lenses into warehouse to obtain finished lenses.

2. The processing technology for optical lenses according to claim 1, characterized in that, In step 1, during the process of obtaining a qualified blank lens, the items to be inspected for the blank glass lens include center thickness, radius of curvature, thickness difference, and appearance; among which, the center thickness is measured using a micrometer, and the radius of curvature is measured using a sag gauge. In the process of obtaining the finely ground lens, rough grinding uses diamond grinding wheels with a grit size of D46-D64, a grinding linear speed of 25-50 m / s, a feed rate of 500-1500 mm / min, and a cutting depth of 0.03-0.08 mm; fine grinding uses diamond grinding discs with a grit size of W28-W14, a grinding pressure of 0.1-0.3 MPa, and a grinding speed of 100-600 rpm; both rough and fine grinding processes are cooled by coolant, which is deionized water or water-based coolant, with a coolant flow rate of 5-20 L / min and a coolant temperature controlled at 15-25℃.

3. The optical lens processing technology according to claim 2, characterized in that, In step 2, during the process of obtaining a polished lens with an amorphous silicon dioxide layer, the polishing slurry is a polishing slurry containing cerium oxide abrasive. The particle size of the cerium oxide abrasive is 0.01-0.1 μm, the mass concentration of cerium oxide in the polishing slurry is 5%-30%, the pH value of the polishing slurry is 7-11, the polishing pressure is 0.05-0.15 MPa, the polishing speed is 50-150 rpm, and the polishing time is 5-30 min. The polishing pad is a polyurethane polishing pad with a hardness of 50-80 Shore A. The polishing slurry supply rate is 10-50 mL / min; the thickness of the amorphous silicon dioxide layer is measured by an ellipsometry and controlled within 1-100 nm; the polishing pad thickness is 0.5-2.0 mm, and the surface of the polishing pad is provided with concentric circular grooves or grid-like grooves with a groove depth of 0.3-1.0 mm; the polishing slurry temperature is controlled within 15-30℃ during the polishing process.

4. The processing technology for optical lenses according to claim 3, characterized in that, In step 3, during the process of obtaining the edge-ground lens, the peelable temporary protective layer is applied to the edge area of ​​the polished lens using a thermosetting hydrolytic protective ink with a viscosity of 5000-8000 mPa·s. The ink is screen-printed with a mesh count of 100-300, resulting in a dry film thickness of 15-20 μm. The curing conditions are baking at 120-180℃ for 20-30 min. The screen printing stencil is a ring shape, with the inner diameter of the ring being 0.5-2 mm smaller than the outer diameter of the optically effective area of ​​the lens. This ensures that the protective layer covers the edge area of ​​the optically effective surface, while the edge-ground area of ​​the lens remains exposed. During the edge grinding process, the grinding depth of the chamfering grinding wheel is 0.05-0.15mm, the feed speed is 0.5-2mm / min, and coolant is continuously sprayed during the edge grinding process. The coolant is deionized water, the coolant temperature is 10-20℃, and the coolant flow rate is 3-10L / min. The temporary protective layer is removed after edge grinding by rinsing the lens in clean water to dissolve and remove it. Deionized water is used for rinsing at a temperature of 20-40℃ for 1-5 minutes at a pressure of 0.1-0.3MPa. After removing the protective layer, ultrasonic cleaning with deionized water is performed at a power of 200-400W for 3-8 minutes.

5. The optical lens processing technology according to claim 4, characterized in that, In step 4, during the process of obtaining the activated lens, argon is used as the working gas for ion beam activation treatment, with an accelerating voltage of 300-600V, an accelerating current of 100-300mA, a treatment time of 1-10min, and a vacuum chamber pressure of 1×10⁻³-9×10⁻³Pa. An ion beam source with a beam diameter of 50-200mm is used. The lens rotates at 5-20rpm during ion beam activation treatment, and the ion beam incident angle is 30-60°. Coating is performed within 30min after ion beam activation treatment. The argon purity is ≥99.999%. The activation effect is confirmed by contact angle measurement after ion beam activation treatment, and the contact angle of the activated lens surface is ≤10°.

6. The processing technology for optical lenses according to claim 5, characterized in that, In step 5, during the process of obtaining the coated lens, the coating is performed by electron beam evaporation, the pressure in the vacuum chamber is ≤2×10⁻²Pa, the output current of the electron beam is 30-40mA, the deposition rate of the film layer is 0.3-0.8nm / s, the ion-assisted bombardment time is 1-5min, and the anode voltage of the ion source is 200-250V; the material of the film layer is SiO₂ or Al₂O₃ or TiO₂; the thickness of the film layer is 10-100nm; the crucible is a molybdenum crucible; the ion-assisted bombardment uses argon or oxygen, and the gas flow rate is 10-50sccm; the purity of the coating material is 99.99% or higher; before coating, the lens is preheated to 150-250°C and kept warm for 10-30min; after the coating is completed, convective cooling with compressed air is adopted, with a cooling rate of 5-10°C / min, until it is cooled to room temperature.

7. The optical lens processing technology according to claim 6, characterized in that, In step 6, during the process of obtaining the ink-coated lens, the viscosity of the ink used for ink coating is 5000-8000mPa·s, the baking temperature after ink coating is 120°C-180°C, and the baking time is 20-60min; the ink coating is performed by spraying or brushing, and the ink coating thickness is 5-20μm; the ink is epoxy resin type or polyurethane type ink, and the active component of the ink is hydroxyl group or amino group or isocyanate group; the ink is thermally cured; the thermal curing of the ink is carried out in a hot air circulation oven, with a nitrogen or air atmosphere in the oven, and the wind speed is 1-3m / s.

8. The processing technology for optical lenses according to claim 7, characterized in that, In step 7, the items for inspecting the ink-coated lens include outer diameter, center thickness, surface accuracy, ink coating range, ink coating firmness and appearance; wherein, the ink coating firmness is tested by adhesive tape pulling test, the ink coating range is detected by a tool microscope with a detection accuracy of 0.02mm; 3M 600 adhesive tape is used for the ink coating firmness test, the pulling is carried out in a 90° direction, the pulling speed of the adhesive tape in the ink coating firmness test is 50-100mm / s, repeated 3 times, and it is qualified if the ink coating layer does not fall off; the surface accuracy is detected by an interferometer, the detection wavelength of the interferometer is 632.8nm, the number of apertures is ≤0.5, and the irregularity (astigmatism) is ≤0.2.